Taxing Africa for inclusive human development: The mediating role of governance quality - Alex Adegboye; Olayinka Adedayo Erin; Simplice Asongu (African Governance and Development Institute (AGDI), 2021)
Given that the literature on the links between taxation and inclusive human development is ambiguous, it is important to investigate whether the mediating influence of governance in taxation for inclusive development exists. Thus, this study explores the linkages between the governance quality, taxation and inclusive human development (i.e., inequality-adjusted human development index) using the generalized method of moments (GMM) technique to establish the empirical findings on 52 African countries for the period 2010-2018. The following findings are established. First, there is an unconditional positive effect of taxation on inclusive human development. Second, the net effects of taxation on inclusive human development, associated with the interaction of the government revenue with governance quality variables, are positive for the most part. It is then evident that when taxation policies are combined with good governance initiatives, the ultimate impact of inclusive human development is likely to be enhanced.
Keywords: 330; Government revenue; taxation; governance quality; Africa